What Croatian farmers think about situation in agriculture? - LonÄariÄ‡, RuÅ¾ica; LonÄariÄ‡, Zdenko; ToluÅ¡iÄ‡, Zrinka (European Scientific Journal, ESJ, 2016)
Analysis of the attitudes of the Croatian agricultural producers on the situation in agriculture was obtained through a survey carried out in the framework of IPA project â€œContribution of agriculture to a clean environment and healthy foodâ€. The aim of the study was to investigate the individual attitudes of agricultural producers about the basic problems and the situation in the agriculture of Croatia. The study involved 57 agricultural manufacturers from the area of Osijek-Baranja and Vukovar-Srijem County. Respondents are primarily registered as family farms (70%) and crafts (16%). 81% of producers are inscribed in the Register of agricultural producers, 68% are in the VAT system, and 72% receive agricultural subsidies in the form of direct payments. Although general attitudes in Croatian society regarding cooperation in agriculture are pretty complicate and divided, farmers are aware of its benefits (evaluated better than problems). According to them, the main problem in Croatian agriculture are high input prices, slow administration and low market food price. Although farmers blame government and its ministries the most for unfavorable situation in agriculture, in the same time they expect the most improvement driven by government decisions. Farmers see themselves primarily as hardworking, dedicated to their job, nature loving people, but at the same level they are disappointed and underestimated due to current long-standing problems in agriculture.